2014
DOI: 10.5217/ir.2014.12.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Characteristics of Colon Cancer Diagnosed at Primary Health Care Institutions

Abstract: Background/AimsThe purpose of this study was to evaluate the clinicopathologic characteristics of colon cancers detected at the SOK Sokpeynhan Internal Medical Network, a nationwide system of primary health care institutions.MethodsWe analyzed 579 colon cancer patients diagnosed using colonoscopy at the SOK network from January 2011 through December 2012. Cancers from the rectum to the splenic flexure were classified as left colon cancer. Patients over 65 were classified as senior.ResultsThe mean age (±SD) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 8 publications
1
17
1
Order By: Relevance
“…Moreover, arsenic compounds also induce clinical remission in patients with acute promyelocytic leukaemia [24] and dermatological disease [25], and may represent a potential treatment for other cancers [26][27][28][29]. The first proof of the As/Se interaction in relation to cancer was found in mice [30] and rats [31], when As III antagonized the carcinogenic effect of Se IV .…”
Section: Arsenic and Seleniummentioning
confidence: 97%
“…Moreover, arsenic compounds also induce clinical remission in patients with acute promyelocytic leukaemia [24] and dermatological disease [25], and may represent a potential treatment for other cancers [26][27][28][29]. The first proof of the As/Se interaction in relation to cancer was found in mice [30] and rats [31], when As III antagonized the carcinogenic effect of Se IV .…”
Section: Arsenic and Seleniummentioning
confidence: 97%
“…According to the annual report of the Korea Central Cancer Registry, a total of 24,986 CRC cases detected in Korea in 2009, representing 13.0% of all incident cancer cases [3, 4]. CRC is the second and third most common cancer in Korean men and women, respectively [3, 4]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, prevention and the early detection of CRC by colonoscopy have become topics of interest . Screening is performed to identify and remove precursor adenoma and is recommended in those > 50 aged years because of the low incidence of CRC before age of 50 in the general population . However, the incidence and mortality rates of CRC in adults aged < 50 years have been increasing .…”
Section: Introductionmentioning
confidence: 99%
“…3 Screening is performed to identify and remove precursor adenoma and is recommended in those > 50 aged years because of the low incidence of CRC before age of 50 in the general population. [4][5][6][7] However, the incidence and mortality rates of CRC in adults aged < 50 years have been increasing. [8][9][10] Regarding advanced adenoma, several studies have reported the prevalence and risk factors in young adults (< 50 years), when advanced adenoma was defined as an adenoma at least 10 mm in diameter high-grade dysplasia (HGD), villous or tubulovillous histologic characteristics, or any combination thereof.…”
Section: Introductionmentioning
confidence: 99%